TAKWINU AL-HUWIYYAH FI IKTISABI AL-LUGHAH AL-TSANIYAH ‘INDA NORTON BIDIRASATI SHIRDIYAH BIMA’HADI RIYADLUL ‘ULUM WADDA’WAH CONDONG TASIKMALAYA - Nuraeni, Intan; Romadhoni, Moh. Syahrul Zaky; Masruroh, Emas (Jazirah: Jurnal Peradaban dan Kebudayaan, 2022)
Pondok Pesantren riyadlul ulum Wadda'wah is an Islamic educational institution that focuses on two foreign languages, namely Arabic and English. Some of the students get a second language at this boarding school, therefore the boarding school tries to improve their language skills properly and correctly by requiring the students to use Arabic or English in their daily lives. This study tries to answer two objectives, namely knowing how the process of identity formation in second language acquisition uses the narrative inquiry method, and knowing the factors that cause identity formation in second language acquisition.This research is a qualitative research using narrative inquiry method. Because the problems in this study require problem solving with evidence of the truth. Research using data collection methods, namely, interviews, observation, and documentation. The sources in this research consist of primary sources and secondary sources. As for the primary sources, the researcher took the primary sources in this research from the interview with three female students of the fourth semester at riyadlul ulum Wadda'wah is an Islamic educational institution. One of the most important results of this study is that the process of forming identity in acquiring a second language in three grade 4 female students is; The process of identity formation is not direct and not easy, the process is gradual, you have to learn a lot from experience, friends and the environment. In addition, things that influence the formation of their identity are cultural assimilation, hybridity, social interaction, acculturation and the environment.